PENGEMBANGAN MEDIA PEMBELAJARAN E-MODUL BERBASIS FLIPBOOK MAKER PADA MATERI GAYA DAN GERAK KELAS IV SDN BAHAGIA 04 - Apri Utami Parta Santi; Gina Maharani Prasetya (Jurnal Tunas Bangsa, 2022)
The background of this research is the lack of enthusiasm of students, feeling bored and lacking understanding of the learning process. The purpose of this research is to develop e-module learning media based on flipbook maker. This study uses the Research and Development (R&D) and development model modified by Sugiyono namely potentials and problems, data collection, product design, design validation, design revision, and product testing. This learning media is subjected to expert validation tests conducted by material experts, media experts and linguists. Then a product trial was carried out with the research subject, namely class IV B students at SDN Bahagia 04. The results showed that the flipbook maker-based e-module media was "very feasible" from the calculation results of material experts with an average score of 96%, media experts with an average -an average of 94%, and linguists with an average of 86%. The results of the small group trials obtained "very good" results with student responses with an average score of 94.4%. Meanwhile, in the large group trial, students got an average score of 87.8% in the "very good" category. Based on the results of the study, it can be concluded that the flipbook maker-based e-module learning media developed for fourth grade students is "very feasible" for use in learning Natural Sciences (IPA) on force and motion material. Abstrak Latar belakang penelitian ini adalah kurangnya antusias peserta didik, merasa jenuh dan kurang pemahaman pada proses pembelajaran. Adapun tujuan dari penelitian ini adalah mengembangkan media pembelajaran e-modul berbasis flipbook maker. Penelitian ini menggunakan model penelitian dan pengembangan Research and Development (R&D) dan pengembangan yang dimodifikasi oleh Sugiyono yaitu potensi dan masalah, pengumpulan data, desain produk, validasi desain, revisi desain, dan uji coba produk. Media pembelajaran ini dilakukan uji validasi ahli yang dilakukan oleh ahli materi, ahli media dan ahli bahasa. Selanjutnya dilakukan uji coba produk dengan subjek penelitian yaitu peserta didik kelas IV B SDN Bahagia 04. Hasil penelitian menunjukkan bahwa media e-modul berbasis flipbook maker “sangat layak” dari hasil perhitungan ahli materi dengan rata-rata skor 96%, ahli media dengan rata-rata sebesar 94%, dan ahli bahasa dengan rata-rata sebesar 86%. Hasil uji coba kelompok kecil memperoleh hasil “sangat baik” dengan respon siswa dengan rata-rata skor 84,3%. Sedangkan pada uji coba kelompok besar siswa mendapatkan rata-rata skor 87,1% dengan kategori “sangat baik”. Berdasarkan hasil penelitian dapat disimpulkan bahwa media pembelajaran e-modul berbasis flipbook maker yang dikembangkan pada peserta didik kelas IV “sangat layak” untuk digunakan dalam pembelajaran Ilmu Pengetahuan Alam (IPA) pada materi gaya dan gerak.